The risks of indiscriminate use of Femproporex as an appetite inhibitor: a review (Research, Society and Development, 2021)
Obesity is recognized by the World Health Organization (WHO) as excess body fat, which impairs the health and quality of life of individuals. There are several forms and treatments for this disease, which may or may not include drug action. One of the drugs used to treat this disease is Femproporex, which is an appetite suppressant that acts on the central nervous system, causing a feeling of satiety, however, the indiscriminate use of this drug can be understood as a problem. Thus, based on the descriptive-exploratory review methodology, based on 10 different authors whose materials were made available on the Scielo and Pubmed platforms, we sought to highlight the main risks of the excessive use of this drug, as well as the possible role of the professional of pharmacy from the perspective of pharmaceutical care. It was found that the public that most uses this medication are women and the most reported side effects are headache, nausea, insomnia, tremors, among others. Thus, it can be seen that the pharmacist is an extremely important professional, contributing to the dissemination of information and awareness in society, seeking to reduce indiscriminate use and, consequently, the damages resulting from unrestricted use.